The importance of sport event on hotel performance for restarting tourism after COVID-19 - Borovcanin, D.; Cuk, I.; Lesjak, M.; Juvan, E. (societies, 2020)
The aim of this study was to illustrate the importance of major sports events, such as marathons, and their economic impact on hotel performance during these unpredictable times for the events and tourism industry. The analysis was focused on the economic impact of the marathon event on hotel performance in the area hosting the race. For that purpose, we selected the Vienna City Marathon, held yearly in April, as a case. We hypothesized that there will be a higher impact of hotel performance a day prior to the marathon in regard to the hotel performance in multiple nonmarathon occasions. As indicators for hotel performance we have chosen hotel occupancy, revenue per available room, average daily rate and total revenue recorded for: day (always Saturday) prior to the marathon, year average, April average and average Saturday in April. Results from this study revealed significant effects of a marathon on three major hotel performance indicators (i.e., hotel occupancy, revenue per available room and total revenue). Findings from this study could serve the local government or event planners after the current crisis to justify financial investments in hosting a marathon or similar sports events for restarting tourism.